2019
DOI: 10.1002/jcb.28968
|View full text |Cite
|
Sign up to set email alerts
|

Magnolol induces apoptosis in osteosarcoma cells via G0/G1 phase arrest and p53‐mediated mitochondrial pathway

Abstract: Osteosarcoma is a highly invasive primary malignancy of bone. Magnolol is biologically active, which shows antitumor effects in a variety of cancer cell lines. However, it has not been elucidated magnolol's effects on human osteosarcoma cells (HOC). This study aimed to determine antitumor activity of magnolol and illustrate the molecular mechanism in HOC. Magnolol showed significant inhibition effect of growth on MG‐63 and 143B cells and induced apoptosis and cell cycle arrest at G0/G1. In osteosarcoma cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Magnolol is a natural neolignan from magnolia plants and is reported to present antitumor, anti-oxidative, anti-inflammatory, and antibacterial effects ( 8 ). The antitumor properties of magnolol were reported to be related but not limited to the PI3K-AKT, p53, NF-κB, and p53-mediated mitochondrial pathways ( 9 , 10 , 22 , 23 ). Unlike well-reported anti-proliferative effects, the anti-metastasis effects of magnolol are not as well studied.…”
Section: Discussionmentioning
confidence: 99%
“…Magnolol is a natural neolignan from magnolia plants and is reported to present antitumor, anti-oxidative, anti-inflammatory, and antibacterial effects ( 8 ). The antitumor properties of magnolol were reported to be related but not limited to the PI3K-AKT, p53, NF-κB, and p53-mediated mitochondrial pathways ( 9 , 10 , 22 , 23 ). Unlike well-reported anti-proliferative effects, the anti-metastasis effects of magnolol are not as well studied.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular ROS are mainly produced from mitochondria. Intracellular or extracellular stimuli lead to intracellular ROS production and increased membrane permeabilization, whereas excessively high levels of ROS promote cell apoptosis by activating internal and external pathways (28). ROS interact with many factors that directly affect cell viability and promote cell death, thus, ROS are widely studied as antitumor agents (29).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, many studies demonstrated that magnolol has antitumor effects in many cancer cell lines [10][11][12][13]. Therefore, we examined the effect of a sublethal concentration of magnolol on the sensitivity to TRAIL in renal carcinoma Caki-1 cells.…”
Section: Magnolol Enhances Sensitivity To Trail In Human Renal Carcinmentioning
confidence: 99%
“…Multiple studies demonstrate the anticancer function of magnolol. Magnolol induces apoptosis through regulation of the mitochondrial pathway in osteosarcoma, renal cancer and gastric adenocarcinoma [10][11][12]. Magnolol also induces cell cycle arrest and apoptosis via p21-or p27-dependent G2/M phase cell cycle arrest [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%